2016
DOI: 10.1098/rsos.160552
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite nanotube-based electrospun ceramic nanofibre mat: a novel support for zeolite membranes

Abstract: Some key parameters of supports such as porosity, pore shape and size are of great importance for fabrication and performance of zeolite membranes. In this study, we fabricated millimetre-thick, self-standing electrospun ceramic nanofibre mats and employed them as a novel support for zeolite membranes. The nanofibre mats were prepared by electrospinning a halloysite nanotubes/polyvinyl pyrrolidone composite followed by a programmed sintering process. The interwoven nanofibre mats possess up to 80% porosity, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…One central challenge pertains to the optimization of this spinning process. To date, various work has been completed to investigate the influence of processing parameters on the electrospinning of different materials, including collagen [10,11], wheat gluten [11], polystyrene [12], polycaprolactone [13], poly(L-lactide-co-epsilon-caprolactone) [14], chitosan-gelatin blend [15], poly(vinyl alcohol) [16], polylactide [16], polydimethlsiloxane [17], polyamide [18,19], silica [20], silk fibroin [21], peptide-based supramolecular polymers [22], and halloysite nanotubes/polyvinylpyrrolidone composite [23]. However, research on the electrospinning of poly(D,L)-lactide-co-glycolide (PLGA) has been few.…”
Section: Introductionmentioning
confidence: 99%
“…One central challenge pertains to the optimization of this spinning process. To date, various work has been completed to investigate the influence of processing parameters on the electrospinning of different materials, including collagen [10,11], wheat gluten [11], polystyrene [12], polycaprolactone [13], poly(L-lactide-co-epsilon-caprolactone) [14], chitosan-gelatin blend [15], poly(vinyl alcohol) [16], polylactide [16], polydimethlsiloxane [17], polyamide [18,19], silica [20], silk fibroin [21], peptide-based supramolecular polymers [22], and halloysite nanotubes/polyvinylpyrrolidone composite [23]. However, research on the electrospinning of poly(D,L)-lactide-co-glycolide (PLGA) has been few.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 82 ] produced low-cost halloysite-based ceramic nanofiber mats by electrospinning and sintering for use as support in zeolite membranes. The new ceramic materials were characterized by higher interconnected porosity, mechanical strength, flux and adhesion compared to the a-Al 2 O 3 commercial support of zeolite.…”
Section: Summarizing Papers and Discussionmentioning
confidence: 99%
“…Through the dispersion of natural nanotube structural clays, it is convenient to obtain uniform nanotube structure for wider applications [13]. It was found that even small loadings of HNTs were sufficient to make significant changes in the polymer properties [14]. In particular, the surface morphology is very sensitive to the nature of the polymer [8].…”
Section: Introductionmentioning
confidence: 99%